Emerging applications of porous organic polymers in visible-light photocatalysis. Issue 15 (31st March 2020) - Wang, Tian-Xiong; Liang, Hai-Peng; Anito, Dejene Assefa; Ding, Xuesong; Han, Bao-Hang
Abstract : Porous organic polymers are efficient photocatalysts in organic synthesis, hydrogen evolution, CO2 reduction, and degradation of organic pollutants. Abstract : Porous organic polymers (POPs) are emerging porous solids featuring high porosity, low density, diverse composition, facile functionalization, and high thermal/chemical stability. POPs are proven competitive candidates in various applications, such as sorption/separation, energy storage, biomedical applications, optical devices, and catalysis. Photocatalysis enables multifarious transformations of chemicals under mild conditions without enormous energy consumption and contaminant generation. Catalytically active species can be incorporated into POPs by means of covalent bonding or metal–ligand coordination, and the catalytic power of POPs can be fine tuned by modulating the electronic properties of monomers and pore structures of the solids, which make POP-based heterogeneous photocatalysts designable for task-specific applications. The outstanding performance and reusability distinguish POPs from their homogeneous analogues. As a result, their catalytic efficiency can be significantly enhanced and cost would be considerably reduced. In this review, we aim to highlight the recent research of POPs in visible-light-driven photocatalysis, including organic synthesis, hydrogen evolution, carbon dioxide reduction, and degradation of organic pollutants. Technological concerns over the hindrance of preparation, post-processing, performance optimization, cost and energy consumption are also discussed.